High-Throughput Metabolomics Method for Discovering Metabolic Biomarkers and Pathways to Reveal Effects and Molecular Mechanism of Ethanol Extract From Epimedium Against Osteoporosis - Zhao, Jun-feng; Xu, Jian-yu; Xu, Yi-er; Chen, Shui-lin; Guo, Yan-xing; Gao, Quan-yang; Sun, Gui-cai (Frontiers in Pharmacology, 2020)
Metabolomics is an effective strategy to explore the molecular mechanism of herbal medicine. Epimedium, a traditional Chinese herb, has a therapeutic effect on osteoporosis (OP), however the molecular mechanism of the anti-OP effect of epimedium is still little known. In this study, we investigated the pharmacological effect and action mechanism of ethanol extract of epimedium (Ext-epi) on OP rat model by metabolomics method for discovering metabolic biomarkers and pathways to reveal the possible targets. The serum of OP rats was analyzed utilized UPLC-Q-TOF/MS metabolomics, and the potential biomarkers were screened and identified using multivariate data analysis systems and network databases. To further appraise the influence of Ext-epi on biological markers and metabolic pathways, and reveal the potential mechanism of Ext-epi on OP treatment. The results showed that 46 potential biomarkers were screened out and after intervention with Ext-epi extracts solution, 16 potential biomarkers were significantly recalled. Further pathway experiments showed that key pathway analysis includes arachidonic acid metabolism, glycerolphospholipid metabolism as potential targets which is related with the efficacy of Ext-epi protect against OP. These results explain the correlation between metabolites and molecular mechanisms, which is of great significance for understanding the intervention of Ext-epi on OP. In short, based on UPLC-Q-TOF/MS metabolomics may provide effective strategies for understanding the pathogenesis of diseases and evaluating the intervention effect of natural products.